Study of Physico-Chemical Characteristics of Wastewater in an Urban Agglomeration in Romania - Paula Popa; Mihaela Timofti; Mirela Voiculescu; Silvia Dragan; Catalin Trif; Lucian P. Georgescu (The Scientific World Journal)
This study investigates the level of wastewater pollution by analyzing its chemical characteristics at five wastewater collectors. Samples are collected before they discharge into the Danube during a monitoring campaign of two weeks. Organic and inorganic compounds, heavy metals, and biogenic compounds have been analyzed using potentiometric and spectrophotometric methods. Experimental results show that the quality of wastewater varies from site to site and it greatly depends on the origin of the wastewater. Correlation analysis was used in order to identify possible relationships between concentrations of various analyzed parameters, which could be used in selecting the appropriate method for wastewater treatment to be implemented at wastewater plants.